Sopan Santun sebagai Cermin Etika Pancasila: Menanamkan Nilai Kemanusiaan di Kalangan Remaja - Wahyuni, Wahyuni; Alfyoni, Ghisanie Azahra; Mulya, Raynata Danielle; Maharani, Amalia Putri; Azzura, Chiatha Destalova; Tumanggor, Raja Oloan (Al-DYAS, 2025)
Politeness is a reflection of the noble values ​​adopted by a nation. Pancasila as the foundation of the state, contains ethical values ​​that are very relevant to practice in everyday life. The shift in moral values, especially for the younger generation, threatens the sustainability of politeness rooted in the values ​​of Pancasila. This community service was carried out for the purpose of instilling humanitarian values ​​in the younger generation of teenagers at SMA X Jakarta Pusat. This community service was given to one class consisting of 37 students and counseling was carried out using Power Point. The results of this community service can be said to be successful and went well and smoothly. This can be seen from the answers to the quiz and their understanding of the material that had been presented.